Dissonance of Choice: Biomedical and Lived Perspectives on HIV Treatment-Taking. Issue 8 (16th November 2020) - Horter, Shona; Seeley, Janet; Bernays, Sarah; Kerschberger, Bernhard; Lukhele, Nomthandazo; Wringe, Alison
ABSTRACT: Treat-all recommends prompt treatment initiation for those diagnosed HIV positive, requiring adaptations to individuals' behavior and practice. Drawing on data from a longitudinal qualitative study in Eswatini, we examine the choice to initiate treatment when asymptomatic, the dissonance between the biomedical logic surrounding Treat-all and individuals' conceptions of treatment necessity, and the navigation over time of ongoing engagement with care. We reflect on the perspectives of healthcare workers, responsible for implementing Treat-all and holding a duty of care for their patients. We explore how the potentially differing needs and priorities of individuals and the public health agenda are navigated and reconciled. Rationalities regarding treatment-taking extend beyond the biomedical realm, requiring adjustments to sense of self and identity, and decision-making that is situated and socially embedded. Sense of choice and ownership for this process is important for individuals' engagement with treatment and care.